The Effect of Compensationa and Communication on Performance Through Employee Job Satisfaction As Variable Mediation at the Department of Finance, Asset, Management and Revenue District Sukoharjo - Sari, Pipit Rafika (STIE AUB Surakarta)
This study aimed to analyze the effect of compensation and communication to employee performance through job satisfaction as a mediating variable in the Department of Finance and Asset Management Revenue District Sukoharjo. The analytical method used is by using validity and reliability test, linearity test, regression analysis, path analysis, t test, F test, test the coefficient of determination and correlation analysis.Compensation Hypothesis Test results positive and significant impact on job satisfaction. Communications positive and significant impact on job satisfaction. Compensation positive and significant impact on the performance of Employees. Communications positive and significant impact on employee performance. Job satisfaction and significant positive effect on employee performance. F test can be concluded jointly independent variable significant effect on employee performance Revenue Service Finance and Asset Management District Sukoharjo. Results R2 value totaling 0.937 variation can be interpreted Employee Performance Revenue Service Finance and Asset Management District Sukoharjo explained by variable compensation, communication, and job satisfaction as an intervening variable amounted to 93.7%. Results of path analysis showed that: Compensation is not effective to improve performance. Effective communication to improve performance.Keywords : Compensation, Communication, Job Satisfaction, Employee Performance